Federal funding of health policy in Brazil: trends and challenges - Cristiani Vieira Machado; Luciana Dias de Lima; Carla Lourenço Tavares de Andrade (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The article analyzes Federal funding of health policy in Brazil in the 2000s, focusing on the Ministry of Health's budget implementation. Federal spending on health was less unstable between 2000 and 2002 and has expanded since 2006. However, it fluctuated as a share of both the Gross Domestic Product and Gross National Revenue. Federal intergovernmental transfers increased, exceeding 70% in 2007. Meanwhile, the proportion of Federal investments remained low, varying from 3.4% to 6.3%. The highest absolute amount of spending was on specialized outpatient and hospital care. The decade showed a proportionally greater increase in spending on pharmaceutical care. The growing allocation of Federal funds to States in the North and Northeast, especially for primary care and epidemiological surveillance, failed to offset the sharp regional inequalities in per capita Federal spending. The main characteristics of health funding limit Federal health policy governance and pose several challenges for the Brazilian Unified National Health System.